أهمية التسويق الدولي في تحديد البدائل الاستراتيجية لاقتحام الأسواق الدولية - بن حوحو, محمد; بن جروة, حكيم (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى تحديد ومعرفة مدى أهمية التسويق الدولي في تحديد البدائل الإستراتيجية لاقتحام الأسواق الدولية، لاسيما وأن هذا الأمر أصبح من بين الأمور التي يجب وضعها في أولويات أهداف أي مؤسسة، خاصة وأن العولمة جعلت جميع أسواق العالم ميدانا مفتوحا لأي مؤسسة ومجالا واسعا لاكتشاف الفرص التسويقية واستغلالها فالأسواق المحلية لم تعد تفي بالغرض وقد تكون فيها أحيانا منافسة شرسة لا يمكن للمؤسسة أن تحقق فيها أهدافها. إلا أن المهمة ليست أمرا هينا بل هي في غاية الصعوبة فالأسواق الدولية تتسم بالتعقيد وتتطلب دراسة وإحاطة بجميع المتغيرات القانونية والاجتماعية والثقافية والاقتصادية والتنافسية ...الخ، إضافة إلى ضرورة توفير الإمكانيات اللازمة لاسيما رؤوس الأموال والكفاءات والخبرة التسويقية، كما تلعب الإستراتيجية دورا مهما في اقتحام الأسواق الدولية من خلال تحديد أجزاء سوق المؤسسة بدقة ووضع المزيج التسويقي الذي يلبي حاجات ورغبات المستهلك بطريقة أفضل من المنافسين. This study aims to identify and know the importance of international marketing in identifying strategic alternatives to break into the international markets, especially as this has become one of the things that must be placed in the priorities of the objectives of any institution, especially as globalization has made all markets in the world an open field for any institution Marketing and exploitation, local markets are no longer adequate and may sometimes be fierce competition in which the organization cannot achieve its objectives. But the task is not easy, but it is very difficult International markets are complex and require study and briefing all the variables of legal, social, cultural, economic and competitive ... Etc, in addition to the need to provide the necessary capabilities, especially capital and competencies and marketing expertise, and the strategy plays an important role in breaking into International markets by carefully identifying the parts of the enterprise market and developing a marketing mix that best meets the needs and desires of the consumer
The importance of international marketing in identifying strategic alternatives to break into international markets
مقال
Keywords: تسويق دولي، إستراتيجية، الأسواق الدولية.; International marketing, strategy, international markets.